Effect of intermediate supports location on natural frequencies of multiple cracked continuous beams - Nam, Do; Khiem, Nguyen Tien; Toan, Le Khanh; Thao, Nguyen Thi; Lien, Pham Thi Ba (Vietnam Journal of Mechanics, 2018)
The present paper deals with free vibration of multiple cracked continuous beams with intermediate rigid supports. A simplified method is proposed to obtain general solution of free vibration in cracked beam with intermediate supports that is then used for natural frequency analysis of the beam in dependence upon cracks and support locations. Numerical results show that the support location or ratio of span lengths in combination with cracks makes a significant effect on eigenfrequency spectrum of beam. The discovered effects of support locations on eigenfrequency spectrum of cracked continuous beam are useful for detecting not only cracks but also positions of vanishing deflection on the beam.